Differential regulation of matrix metalloproteinases in varicella zoster virus-infected human brain vascular adventitial fibroblasts - Nagel, Maria A. (J Neurol Sci, 2015)
Upon reactivation, varicella zoster virus (VZV) spreads transaxonally, infects cerebral arteries and causes ischemic or hemorrhagic stroke, as well as aneurysms. The mechanism(s) of VZV-induced aneurysm formation is unknown. However, matrix metalloproteinases (MMPs), which digest extracellular structural proteins in the artery wall, play a role in cerebral and aortic artery aneurysm formation and rupture. Here, we examined the effect of VZV infection on expression of MMP-1, -2, -3, and -9 in primary human brain vascular adventitial fibroblasts (BRAFS). At 6 days post-infection, VZV- and mock-infected BRAFs were analyzed for mRNA levels of MMP-1, -2, -3 and -9 by RT-PCR and for corresponding total intra- and extracellular protein levels by multiplex ELISA. The activity of MMP-1 was also measured in a substrate cleavage assay. Compared to mock-infected BRAFs, MMP-1, MMP-3 and MMP-9 transcripts, cell lysate protein and conditioned supernatant protein were all increased in VZV-infected BRAFs, whereas MMP-2 transcripts, cell lysate protein and conditioned supernatant protein were decreased. MMP-1 from the conditioned supernatant of VZV-infected BRAFs showed increased cleavage activity on an MMP-1-specific substrate compared to mock-infected BRAFs. Differential regulation of MMPs in VZV-infected BRAFs may contribute to aneurysm formation in VZV vasculopathy.